The swan thieves : a novel - Kostova, Elizabeth (Little, Brown and Co., 2009)
Psychiatrist Andrew Marlowe, devoted to his profession and the painting hobby he loves, has a solitary but ordered life. When renowned painter Robert Oliver attacks a canvas in the National Gallery of Art and becomes his patient, Marlow finds that order destroyed. Desperate to understand the secret that torments the genius, he embarks on a journey that leads him into the lives of the women closest to Oliver and a tragedy at the heart of French Impressionism.